Meningkatkan Hasil Belajar Siswa Melalui Pemanfaatan Media Pembelajaran Flashcard di Kelas I SDN 5 Limboto - Nurul Syahril; Abd. Kadim Masaong; Nursyaida (Research Review: Jurnal Ilmiah Multidisiplin, 2026)
This study aimed to improve students' learning outcomes in Indonesian Language subject through the use of flash card learning media in Grade I of SDN 5 Limboto. The findings indicated that most students had not achieved the minimum mastery criterion of 75, with the classical learning mastery rate only 16.67%. The low learning outcomes were attributed to the limited use of engaging instructional media and low level of student participation during the learning process. This study employed classroom action research based on the Kemmis and McTaggart model, which was conducted in two cycles consisting of planning, action, observation, and reflection. The participants were 24 first-grade students. Data were collected through classroom observation, achievement and documentation. The data were analyzed using both quantitative and qualitative descriptive approaches. The findings revealed a gradual improvement in students' learning outcomes throughout the implementation of the research. In the preliminary observation, the classical learning mastery rate was only 16.67%. It increased to 65% in Cycle I and reached 96% in Cycle II, with 23 students demonstrating improved learning outcomes. Both teacher and student classroom activities showed significant improvement, as reflected in increased student participation, greater confidence answering questions, and better reading and writing skills. The use of flash card learning media was effective in improving students' learning outcomes in Indonesian Language subject for Grade I students at SDN 5 Limboto. The use of flash cards created more engaging, interactive, and developmentally appropriate learning environment that supported the learning characteristics of elementary school students.